EPIDEMIOLOGICAL AND CLINICAL ASPECTS OF THE SCHISTOSOMA MANSONI (CIPEEX, 2025)
The present study aimed to review the clinical and epidemiological aspects of Schistosoma mansoni infection, with emphasis on endemic regions. Schistosomiasis is a parasitic disease that remains one of the leading causes of morbidity worldwide, affecting more than 250 million people in 78 countries and causing up to 500,000 deaths annually, second only to malaria. In Brazil, Schistosoma mansoni is the primary cause, particularly in areas with inadequate sanitation.Transmission occurs through contact with contaminated water, where snails of the genus Biomphalaria act as intermediate hosts. Despite advancements in control, schistosomiasis continues to be a serious public health issue in endemic regions. Its heteroxenic biological cycle involves humans as definitive hosts, with the parasite affecting the hepatic portal system. Symptoms include pruritus and redness at the site of penetration of cercariae (the infective larva for humans), as well as fever, headache, chills, sweating, weakness, lack of appetite, muscle pain, cough, diarrhea, nausea, and vomiting.After two months of infection, symptoms may progress to include alternating diarrhea and intestinal constipation, melena, dizziness, palpitations, weight loss, and hepatomegaly. Severe cases can lead to ascites, digestive bleeding, and pulmonary and portal hypertension.The study highlights the importance of continued investigation into schistosomiasis caused by Schistosoma mansoni, given its significant impact on public health. Affected areas are often characterized by inadequate sanitary infrastructure and direct population contact with contaminated water. Control programs using Praziquantel have successfully reduced parasite loads. However, challenges such as reinfection and persistent transmission foci in riverside areas hinder disease eradication. Moreover, the lack of effective control over the intermediate host, Biomphalaria snails, remains a major obstacle to interrupting the transmission cycle.
Keywords: Schistosoma mansoni; Schistosomiasis; Basic sanitation